1990
DOI: 10.1007/bf01969020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of histamine H3-antagonists on human leukocytes

Abstract: To determine the role of the histamine H3-receptor on basophils, different specific H3-antagonists were investigated. Incubation of washed leukocytes with N alpha-acylated histamine-derivatives (N alpha-ahd) induced elevated histamine levels. This process turned out to be dependent on dose, time and temperature, but independent of Ca2+ and Mg2+ ions. IgE-mediated histamine release was not modulated. [3H]-L-histidine was not decarboxylated into [3H]-histamine in spite of the observed histamine increase. Highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The effect of RAMHA and thioperamide on histamine release from human adenoidal mast cells has been studied. 17 RAMHA had no effect, but thioperamide increased spontaneous and decreased concanavalin Ainduced histamine release. Its spontaneous histaminereleasing effect was thought to indicate the presence of the H 3 receptor, but the differing effects on stimulated and unstimulated cells suggested that H 3 -independent mechanisms may be involved.…”
Section: Discussionmentioning
confidence: 87%
“…The effect of RAMHA and thioperamide on histamine release from human adenoidal mast cells has been studied. 17 RAMHA had no effect, but thioperamide increased spontaneous and decreased concanavalin Ainduced histamine release. Its spontaneous histaminereleasing effect was thought to indicate the presence of the H 3 receptor, but the differing effects on stimulated and unstimulated cells suggested that H 3 -independent mechanisms may be involved.…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with these reports, we found that cimetidine, an H 2 -histamine receptor antagonist, abolished the increased expresion of PDE4B induced by histamine whilst dexchlorpheniramine, an H 1 -antihistamine, was not effective. H 3 -histamine receptor antagonists were not tested since the existence of this class of histamine receptors on human neutrophils seems unlikely [43,44] In addition, we examined whether the up-regulation by histamine of PDE4 activity in human neutrophils had an impact on their functional responsiveness to a different autacoid, PGE 2 , which also acts by increasing cAMP in human neutrophils following stimulation of EP 2 receptors coupled to adenylyl cyclase [45]. As demonstrated in concentrationresponse studies, pretreatment of cells with histamine substantially decreased the ability of PGE 2 to inhibit the SOZ-induced release of superoxide anion.…”
Section: Discussionmentioning
confidence: 99%
“…The H2R‐mediated inhibitory actions of histamine is more prominent in basophils than in mast cells . H3R does not seem to affect basophil functions . H4R expression has been shown on human mast cells and basophils .…”
Section: Inhibitory Receptors On Human Mast Cells and Basophilsmentioning
confidence: 99%
“…[159][160][161] H3R does not seem to affect basophil functions. 162,163 H4R expression has been shown on human mast cells and basophils. 164,165 H4R activation can modulate the function of mast cells and basophils.…”
Section: Histamine Receptorsmentioning
confidence: 99%